An Operation Strategy of the Hybrid Multi-Terminal HVDC for Contingency - Hwang, Sungchul; Song, Sungyoon; Jang, Gilsoo; Yoon, Minhan (Energies (Basel), 2019)
The application of the direct current (DC) transmission is increasing through the interconnection between grids or the renewable energy resource integration. Various types of DC transmission topology are researched, and the hybrid multi-terminal high voltage DC (HVDC), called the “MTDC”, is one of the research subjects. The hybrid multi-terminal HVDC is the MTDC system that is composed with the Line Commutated Converter (LCC) and Voltage Source Converter (VSC). Most hybrid MTDC research has been focused on the connection of the renewable energy generation sources, especially offshore wind farms. However, the DC grid built with a hybrid MTDC was recently proposed due to the development of the converter technology. Therefore, the DC grid is expected to be able to substitute some parts of the transmission grid instead of the alternating current (AC) system, and the operation strategies of the DC grid are still being researched. The DC grid has the advantage of being able to control the power flow, which can even improve the stability of the connected AC system. The dynamic model is required to analyze the improvement of the AC system by the operation strategy of the hybrid MTDC, however, there is no generic model for the system. In this paper, an operation strategy of the hybrid MTDC is proposed to improve the stability of the AC power system by increasing the utilization of parallel AC transmission lines under the contingency condition. Furthermore, studies on the modeling method for a hybrid MTDC analysis were performed. The proposed modeling method and operation strategy were verified in simulations for which a modified IEEE 39 bus test system was used. The improvement of transient stability by the proposed hybrid MTDC system was shown in the simulation results.